Strengthening Economic Rights and Women's Occupational Choice : The Impact of Reforming Ethiopia's Family Law - Hallward-Driemeier, Mary; Gajigo, Ousman (World Bank, Washington, DC, 2014)
This paper evaluates the impact of strengthening legal rights on the types of economic opportunities that are pursued. Ethiopia changed its family law, requiring both spouses' consent in the administration of marital property, removing the ability of a spouse to deny permission for the other to work outside the home, and raising women's minimum age of marriage. Thus both access to resources and the removal of restrictions on employment served to strengthen women's bargaining position within the household and their ability to pursue economic opportunities. Although this reform now applies nationally, it was initially rolled out in the two chartered cities and three of Ethiopia's nine regions. Using nationally representative household surveys from just prior to the reform and five years later allows for a difference-in-difference estimation of the reform's impact. The analysis finds that women were relatively more likely to work in occupations that require work outside the home, employ more educated workers, and in paid and full-time jobs where the reform had been enacted, controlling for time and location effects. As the relative increase in women's participation in these activities was 15-24 percent higher in areas where the reform was carried out, the magnitude of the impact is significant too.